The Influence of the Integration with the European Union on Central and Eastern European Countries' Agricultural Productivity - Baer-Nawrocka, Agnieszka; Kiryluk-Dryjska, Ewa (Publishing House of the Wrocław University of Economics, 2009)
The objective of this article is to illustrate and compare changes in agricultural productivity of Central and Eastern European Countries between 2002 (pre-accession period) and 2008 (post-accession period). In most studies in order to assess the productivity of agriculture, partial effectiveness of particular production factor is calculated. In agricultural sector the labour, land, capital are the main production factors, thus the agricultural production is a result of synergy of those three components in the production process. The analysis conducted in this paper proves that the growth of agriculture productivity indexes may be observed in all analyzed countries. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 13-21